2003
DOI: 10.1002/food.200390043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of solvents on the antioxidant property of flavonoids

Abstract: In polyphenols redox systems, the solvent plays a fundamental role in the chemical behaviour of these compounds. Antioxidants can react in different ways with the prooxidant molecules. We have found differences in the antioxidant capacity of flavonoids such as naringin, neohesperidin, neoericitrin, hesperidin, narirutin didymin and the related flavones naringenin, hesperetin eriodictyol and isosakuatenin, when they are in the presence of radicals and solved in water or in an alcohol mixture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 14 publications
1
38
0
6
Order By: Relevance
“…The number of -OH groups and their positions on the ring are important for both flavonoids and phenols. From the study of the resonance structures formed during the oxidation processes, it can be observed that the ortho-and para-substitutes of the radicals are more stable than the meta-substitute (Finotti & Di Majo, 2003). In particular, ortho-diphenolic substitution gives high antioxidant ability, while a single hydroxyl substitution, as in tyrosol, does not confer any activity, since tyrosol does not protect LDL from chemically induced oxidation.…”
Section: The Antioxidant Activity Of the Polyphenolic Compoundsmentioning
confidence: 99%
“…The number of -OH groups and their positions on the ring are important for both flavonoids and phenols. From the study of the resonance structures formed during the oxidation processes, it can be observed that the ortho-and para-substitutes of the radicals are more stable than the meta-substitute (Finotti & Di Majo, 2003). In particular, ortho-diphenolic substitution gives high antioxidant ability, while a single hydroxyl substitution, as in tyrosol, does not confer any activity, since tyrosol does not protect LDL from chemically induced oxidation.…”
Section: The Antioxidant Activity Of the Polyphenolic Compoundsmentioning
confidence: 99%
“…On the other hand, the majority of antioxidant assays of hesperidin were carried out by using either the Crocin bleaching inhibition method (Finotti & Majo, 2003), the spectrophotometer method (Brand-Williams et al, 1995) or by measuring oxygen radical absorbance capacity (ORAC) (Lin & Chin, 2006). The antioxidant capacity of hesperidin in the present study is found to be moderately active compared with other reports that found hesperidin to be inactive (Garg et al, 2001), or had slow but long-lasting activity (Lee et al, 2002).…”
Section: Hesperidin Concentration and Antioxidant Capacitymentioning
confidence: 99%
“…In polyphenol redox systems the solvents play a fundamental role in the chemical behavior of these compounds, and consequently their antioxidant property. This means that the compounds present different chemical forms related to the environment in which they are solved during the measurement of the antioxidant assay (Pedrielli et al, 2001;Finotti & Majo, 2003). Also, kinetic factors may be of great importance (Foti & Ruberto, 2001).…”
Section: Hesperidin Concentration and Antioxidant Capacitymentioning
confidence: 99%
“…The solubility of flavonoids in fats and oils is very low and their role in the oxidation of oil is not significant; however, they can contribute to decreasing the oxidation of fat in food emulsions [30]. Thus, Finotti and Di Majo [31] reported that all flavonoids show antioxidant activity in hydrophilic environments, but this activity is reduced in lipophilic environments, as is the case with neohesperidin, hesperetin and didymin, while other flavonoids, such as naringin, narirutin or naringenin, become pro-oxidant.…”
Section: Lipids Oxidationmentioning
confidence: 99%